Mangrove plants in coastal area of Central Java: 3. Horizontal and vertical diagram of vegetation profile - AHMAD DWI SETYAWAN; KUSUMO WINARNO (Alm); INDROWURYATNO INDROWURYATNO; WIRYANTO WIRYANTO; ARI SUSILOWATI (Society for Indonesian Biodiversity, 2008)
The study was intended to observe the horizontal and vertical diagrams of mangrove vegetation profile on southern and northern coast of Central Java Province. This research was conducted in July until December 2003, at 20 sites. Analysis of profile diagram was done in Laboratory of Biology Department, Faculty of Mathematics and Natural Sciences, Sebelas Maret University (UNS) Surakarta. Data was collected by using belt transect method, from coast line into landward. The result indicated that the diagram profile of vegetation showed the height of anthropogenic influence, where the vegetation was dominated by young plants; there were only (1)-2-(3-4) strata of canopy (storey). Human disturbance caused most of the vegetation in the secondary succession level; almost it has not in the climax condition level. The area in the belt transect that used to build diagram usually have canopy gap or bare land caused by logging, or to be converse into another land use, especially sawah (rice field) and tambak (fish pond and salt extraction). The resistance of young plant gives hope to the sustainability of the mangrove plant in Central Java, but width scale of environmental changes can degrade this habitat completely.Key words: vegetation profile, horizontal and vertical diagrams, Central Java Province